2012
DOI: 10.1167/iovs.12-10454
|View full text |Cite
|
Sign up to set email alerts
|

Posture-Induced Intraocular Pressure Changes in Eyes with Open-Angle Glaucoma, Primary Angle Closure with or without Glaucoma Medications, and Control Eyes

Abstract: PURPOSE.To compare the posture-induced intraocular pressure (IOP) changes in eyes with open-angle glaucoma (OAG), primary angle closure (PAC) with or without glaucoma medications, and healthy control eyes with normal IOPs. METHODS.The IOP was measured in the sitting position (SP) and the lateral decubitus position (LDP) with a rebound tonometer. The IOP in the LDP was measured in the upper eyes 5 minutes after assuming this posture. RESULTS.Fifty-two patients with OAG, 52 with PAC, and 52 controls with normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…In contrast, our previous results showed that there was no significant difference in the posture-induced IOP changes from the sitting to the lateral decubitus position between patients with POAG and NTG. 31 In the present study, the posture-induced IOP change was 3.3 mm Hg in the nonoperated, medically treated group and 1.0 mm Hg in the surgically treated group. However, it is difficult to compare the magnitude of the posture-induced IOP changes in the different studies because of varying body positions, diseased eye definitions, inclusion criteria, races/ethnicities, IOP measurement techniques, and research methods.…”
Section: Discussionsupporting
confidence: 43%
“…In contrast, our previous results showed that there was no significant difference in the posture-induced IOP changes from the sitting to the lateral decubitus position between patients with POAG and NTG. 31 In the present study, the posture-induced IOP change was 3.3 mm Hg in the nonoperated, medically treated group and 1.0 mm Hg in the surgically treated group. However, it is difficult to compare the magnitude of the posture-induced IOP changes in the different studies because of varying body positions, diseased eye definitions, inclusion criteria, races/ethnicities, IOP measurement techniques, and research methods.…”
Section: Discussionsupporting
confidence: 43%
“…It should be noted, however, that in the present study the IOP measurements were performed with different devices in the GLALE-and control group compared to the GLAIMP-group. Further, a study comparing the LDP-induced IOP changes in open and closed angle glaucoma and healthy controls did not report significant differences in IOP positional changes between the groups 47 . It is difficult to compare our findings to the aforementioned studies because of different methodologies used.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings were comparable with Sawada et al who demonstrated similar IOP changes in different subgroups of open-angle glaucoma, PACG as well as normal control. [9] Our study is the first attempt to study postural changes effect in PACG patients in Indian population subset. Yamabayashi et al also reported similar results where posture-induced IOP changes in OAG patients were more on the average than that in control normal eyes but there was no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Sawada et al compare the posture-induced IOP changes in eyes with open-angle glaucoma, primary angle-closure with or without glaucoma medications, and healthy control eyes with normal IOPs but in Japanese population. [9] us, the purpose of our study was to compare the posture-induced IOP changes among eyes with angle-closure glaucoma with or without medication and control eyes with normal IOPs in Indian population. To the best of our knowledge, this is the first reported study of its kind.…”
mentioning
confidence: 99%